Sosialisasi Makanan Bergizi Pudding Daun Kelor Pencegah Stunting Oleh KKN Kolaboratif Kelompok 222 di Desa Sucopangepok Kecamatan Jelbuk Kabupaten Jember - Aisyah Nur Afifah; Amirotul Urfiyah Zahro; Bayu Akbar Ramadhani; Desi Rahma Suci; Elsa Rahma Dian Nurul Aziza; Ferdy Septian Hidayat; Fharantias Riska Dita Rosa Indrawan; Huda Abdu Aziz Nurdin; Maulina Vella Syafitri; Mukhammad Bahrul Ilmi; Valentino Dimeta Widi; Sukron Makmun (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2023)
Indonesia currently has a stunting rate of 24.4% and the figure is still below the WHO standard which was originally a safe figure for each country said to be good in handling stunting cases at least able to reach 20. The methodology used is socialization and demonstration. The Socialization of Moringa Leaf Pudding Nutritious Food for Stunting Prevention was carried out by 11 222 Group Collaborative KKN Students in Sucopangepok Village, Jelbuk District, Jember Regency accompanied by Village Midwives and Posyandu Cadres. In the implementation of the Collaborative KKN #2 work program, group 222 in Sucopangepok Village went smoothly and the cadres enthusiastically received material about the benefits of Moringa leaves and innovations in Moringa leaf pudding processing. The results of this activity are expected to add to the wealth of science regarding the benefits of Moringa oleifera extract against stunting in toddlers, So that the community can use Moringa leaf plants well, especially to meet the nutrition of toddlers.